Phenotypic Diversity and Emerging New Tools to Study Macrophage Activation in Bacterial Infectious Diseases - Ka, Mignane B.; Daumas, Aurélie; Textoris, Julien; Mege, Jean-Louis (Frontiers in Immunology, 2014)
Macrophage polarization is a concept that has been useful to describe the different features of macrophage activation related to specific functions. Macrophage polarization is responsible for a dichotomic approach (killing versus repair) of the host response to bacteria: M1-type conditions are protective, whereas M2-type conditions are associated with bacterial persistence. The use of the polarization concept to classify the features of macrophage activation in infected patients using transcriptional and/or molecular data and to provide biomarkers for diagnosis and prognosis has most often been unsuccessful. The confrontation of polarization with different clinical situations in which monocytes/macrophages encounter bacteria obliged us to reappraise this concept. With the exception of M2-type infectious diseases such as leprosy and Whipple’s disease, most acute (sepsis) or chronic (Q fever, tuberculosis) infectious diseases do not exhibit polarized monocytes/macrophages. This is also the case for commensals that shape the immune response and for probiotics that alter the immune response independent of macrophage polarization. We propose that the type of myeloid cells (monocytes vs. macrophages) and the kinetics of the immune response (early vs. late responses) are critical variables for understanding macrophage activation in human infectious diseases. Explorating the role of these new markers will provide important tools to better understand complex macrophage physiology.